1995
DOI: 10.1288/00005537-199502000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local epinephrine on cutaneous bloodflow in the human neck

Abstract: The effectiveness of local anesthetics is improved by the addition of a vasoconstrictor which increases duration of action and decreases both systemic toxic reactions and local bleeding. Epinephrine, the standard drug for vasoconstriction, has some limitations due to potential dose-related cardiac and local toxic effects. The authors examined the minimal effective epinephrine concentration required for maximal cutaneous vasoconstriction in the human subject so as to limit potential dose-related side effects. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 8 publications
0
40
0
1
Order By: Relevance
“…O'Malley et al 8 found that 2.5 g/mL produced as much vasoconstriction as 5 g/mL when coinjected with lidocaine 1% into human neck skin, and Siegel et al 7 concluded that even 1.25 g/mL of epinephrine was as effective at reducing the amount of bleeding in rabbit skin injected with lidocaine 1%. In addition, Niemi and Breivik 9 have shown that 1.5 g/mL is optimal for prolonging the pain-relieving effects of epidural bupivacaine, 1 mg/mL, after major surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Malley et al 8 found that 2.5 g/mL produced as much vasoconstriction as 5 g/mL when coinjected with lidocaine 1% into human neck skin, and Siegel et al 7 concluded that even 1.25 g/mL of epinephrine was as effective at reducing the amount of bleeding in rabbit skin injected with lidocaine 1%. In addition, Niemi and Breivik 9 have shown that 1.5 g/mL is optimal for prolonging the pain-relieving effects of epidural bupivacaine, 1 mg/mL, after major surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, it is important to limit the dose of epinephrine as far as possible, and the recommended optimal concentration is usually 5 g/mL (1:200,000), 2,5,6 although 12.5 g/mL (1:80,000) is sometimes used in ear, nose, and throat surgery. However, some studies have shown that lower doses-sometimes as low as 1.25 g/mL (1:800,000)-can also be as effective, [7][8][9] and this disparity could be caused by a combination of fac-tors, including the route of administration, the human or animal model, the use of volatile agents for general anesthesia, the method used to assess effectiveness (i.e., duration of anesthesia, plasma drug levels, extent of vasoconstriction), the measurement period, and the local anesthetic studied.…”
mentioning
confidence: 99%
“…On the other hand, the studies that compared the vasoconstriction effect depending on the ratio of local anesthetic revealed that there was no significant clinical difference, although a wide range of concentrations were tested from 1 : 50,000 to 1 : 400,000 [10,11]. If so, the use of a lower concentration of epinephrine for the vasoconstriction effect can be helpful in reducing various complications.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrate that epinephrine results in equivalent vasoconstriction at concentrations of 1:100,000 and 1:200,000. [37][38][39] Therefore, it is unlikely that the difference in epinephrine concentrations caused any appreciable difference in the amount of lidocaine required to achieve anesthesia in both groups. The 0.5% lidocaine did not require increased volume for effective anesthesia, compared with 1.0% lidocaine.…”
Section: Discussionmentioning
confidence: 99%